Is the Iron Silk Road Really So Important? Rail Freight Use on China’s “Silk Road Economic Belt” - P. Bucsky; T. Kenderdine (Vestnik MGIMO-Universiteta)
CR Express containerised rail transport between Europe and China is a flagship project of China’s “Belt and Road”. Yet operational and financial details of the project remain scarce. Due to poor governance and logistics transparency, the actual quantity of containers and goods transported is essentially unknowable. The authors doubt the efficacy of the CR Express intercontinental rail system and test its real and possible capacity throughputs. In the article they compare China public media statements with European Union statistics and reveal discrepancies between the number of trains supposedly departing China and the number of trains arriving in the European Union. This article provides numerous data sources and estimates on China–Europe rail freight traffic and demonstrates that the actual transported quantity of goods is probably lower than anticipated or reported. The article also analyses the political development of the CR Express rail freight system and China’s wider “Transport Power” policy. It concludes that while the political concept of the CR Express rail freight system is progressive, and the economic development of creating new cumulative causation systems is theoretically possible, that the evidence for actual economic use is underwhelming. This research helps European Union, Russian, and Central Asian policymakers better assess the viability of participating in the continued rollout of China’s CR Express intercontinental rail freight system. The authors warn that while the CR Express system has potential to be an economic good for Central Asian development it exposes the Eurasian economies to China's political and financial risk. For China the CR Express system fulfils only geopolitical and geoeconomic functions, and ultimately participation in the policy is of minimal utility to European Union economies.